1981
DOI: 10.1136/pgmj.57.666.207
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenoreceptor blocking drugs and thyroid hormones in hyperthyroid subjects

Abstract: SummarySerum thyroid hormone concentrations were measured before and during 10 days' treatment with atenolol (200 mg/day), acebutolol (400 mg/day), oxprenolol (160 mg/day) and propranolol (160 mg/day) in 24 hyperthyroid patients. During propranolol treatment serum triiodothyronine (T3) concentrations fell significantly (P < 0 05) but there was no change in thyroid hormone concentrations in the other groups although all patients reported a symptomatic improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The effects of alprenolol on thyroid function were studied in a double-blind placebo-controlled trial in euthyroid subjects with a history of myocardial infarction. 328 The results indicated a direct effect of long-term alprenolol treatment on serum levels of serum T4, T3, and rT3 in euthyroid subjects, resulting in a significant elevation of rT3. After withdrawal, increases were seen in TT4, FT4I, TT3, and FT3I.…”
Section: β-Adrenergic Receptor Blockersmentioning
confidence: 83%
See 1 more Smart Citation
“…The effects of alprenolol on thyroid function were studied in a double-blind placebo-controlled trial in euthyroid subjects with a history of myocardial infarction. 328 The results indicated a direct effect of long-term alprenolol treatment on serum levels of serum T4, T3, and rT3 in euthyroid subjects, resulting in a significant elevation of rT3. After withdrawal, increases were seen in TT4, FT4I, TT3, and FT3I.…”
Section: β-Adrenergic Receptor Blockersmentioning
confidence: 83%
“…T 4 levels are unaffected by atenolol. 328,330 Propranolol. Propranolol, a β-adrenergic blocker, is often used as an adjunct in the treatment of thyrotoxicosis.…”
Section: β-Adrenergic Receptor Blockersmentioning
confidence: 99%
“…Metoprolol is a selective R1-adrenoreceptor blocker with neither ISA nor MSA (Frishman 1981). Practolol (Murchison et al 1976) and oxprenolol (Jones et al 1981) possess some ISA which may explain why these drugs are less effective in reducing the heart rate than other /3-adrenoreceptor blockers without ISA. Although indenolol possesses a weak ISA, it was effective for the amelioration of thyrotoxic tachycardia because of its MSA in addition to its /3-adrenoreceptor blocking activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other non-specific /3-adrenoreceptor blockers, oxprenolol (Jones et al 1981) and sotalol (Wahlberg et al 1976), which had been reported to be ineffective on the serum levels of thyroid hormones, were less potent than propranolol (Frishman 1979). The significant decrease in serum thyroid hormones induced by the treatment with carteolol would be attributed to its stronger /3-adrenoreceptor blocking activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation